"Poemat o zagładzie Lizbony" (1755) i "Kandyd" (1759) czyli Wolter wobec Leibniza - Niedziela, Mateusz (Acta Neophilologica, 2021)
This article deals with the ways Voltaire makes references in his texts to the philosophical thought of Leibniz. To achieve maximum coherence, this paper only discusses those writings by Voltaire that most directly refer to the Leibnizian issues. These are primarily Poem on the Lisbon Disaster and the philosophical tale Candide, or Optimism. The article critically examines various aspects of Leibniz’s philosophy, such as the theory of pre-established harmony and the concept of monads, and above all the notion of the best possible universe. Moreover, selected aspects of Voltaire’s and Leibniz’s thoughts are compared. For the purpose of consistent analysis, the article primarily focuses on those features in the German philosopher’s system that were particularly questioned by the author of Candide.